Age Structures and Air Pollution: What Role Does Gender Play? - Liu, Jiliang; Wang, Wei; Chen, Yin E; Chang, Chun-Ping (Problemy Ekorozwoju, 2019)
We investigate the influence of age structure and gender on air pollution, dividing the age structure into four groups and use CO2 emissions as a measure of air pollution, which can be separated into four categories to obtain more complete findings, then employing panel cointegration techniques and panel-based error correction models. The data are collected from 29 OECD and 40 non-OECD countries in the period 1990-2014. For case of total CO2 emissions, younger (people under 30) and older people (people 65 and above) emit less than people in the intermediate age group, but the impact of age group on CO2 emissions is different when looking at CO2 emissions from coal, gas, and oil. While we take gender into account, the causality between age structure and CO2 emissions becomes significant, especially for the relationship between population and total CO2 emissions in OECD and non-OECD countries. We also note that more people who are aged 15-29 increase total CO2 emissions in OECD countries and more people who are aged 30-44 decrease CO2 emissions from coal in non-OECD countries. Our findings suggest that an energy and environmental policy should consider both age structure and gender effects on environmental issues.